Evaluasi kualitas konseling KB terhadap pemilihan metode kontrasepsi jangka panjang (MKJP) di PMB Desy Fitriyani - Tri Sartika; Tri Restu Handayani (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
The quality of family planning counseling plays an important role in helping clients choose appropriate contraceptive methods, particularly Long-Acting and Permanent Methods (LAPMs). However, the utilization of LAPMs remains lower than that of short-term contraceptive methods. This study aimed to determine the relationship between the quality of family planning counseling and the selection of LAPMs at PMB Desy Fitriyani. This study employed an analytical design with a cross-sectional approach. The study was conducted at PMB Desy Fitriyani in May 2026 and involved 56 respondents selected using the total sampling technique. Data were collected using questionnaires and analyzed through univariate and bivariate analyses using the Chi-Square test with a significance level of α=0.05. The results showed that most respondents perceived the quality of family planning counseling as good (35 respondents; 62.5%), and most respondents chose LAPMs (32 respondents; 57.1%). The Chi-Square test revealed a p-value of 0.002 (p<0.05), indicating a significant relationship between the quality of family planning counseling and the selection of LAPMs. In conclusion, the quality of family planning counseling is associated with the selection of LAPMs. The better the quality of counseling received by clients, the greater the likelihood of choosing LAPMs. Therefore, improving the quality of counseling is essential to support the utilization of LAPMs.